2018
DOI: 10.31661/jbpe.v0i0.676
|View full text |Cite
|
Sign up to set email alerts
|

Mother’s Exposure to Electromagnetic Fields before and during Pregnancy is Associated with Risk of Speech Problems in Offspring

Abstract: Background: Rapid advances in technology, especially in the field of telecommunication, have led to extraordinary levels of mothers’ exposures to radiofrequency electromagnetic fields (RF-EMFs) prior to or during pregnancy.Objective: The main goal of this study was to answer this question whether exposure of women to common sources of RF-EMFs either prior to or during pregnancy is related to speech problems in the offspring.Materials and Methods: In this study, mothers of 110 three-to-seven-year-old children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“… -Fetal temperatures > by 0.025, 0.030, and 0.017 (K) in GA a 13, 18, and 26 wks b respectively. Use one case model V/B Zarei et al, 2019 Iran A cross-sectional design N= 75 mothers of healthy children (control group) and 110 mothers of children aged 3-7 years diagnosed with speech problems GA a = Not determined Associations were found between the use of cordless phones and offspring speech problems for both before pregnancy and during pregnancy maternal exposure (P=0.005 and P=0.014, respectively). Small sample size III/C Yuskel et al, (2016) Turkey An experimental design N=32 rats and their 40-newborn offspring GA a = NA Progesterone, prolactin, and estrogen levels in the 900, 1800, and 2450 MHz/1hr groups were lower compared to the control group (p<0.001, p < 0.05, and p<0.05 respectively).…”
Section: Methodsmentioning
confidence: 99%
“… -Fetal temperatures > by 0.025, 0.030, and 0.017 (K) in GA a 13, 18, and 26 wks b respectively. Use one case model V/B Zarei et al, 2019 Iran A cross-sectional design N= 75 mothers of healthy children (control group) and 110 mothers of children aged 3-7 years diagnosed with speech problems GA a = Not determined Associations were found between the use of cordless phones and offspring speech problems for both before pregnancy and during pregnancy maternal exposure (P=0.005 and P=0.014, respectively). Small sample size III/C Yuskel et al, (2016) Turkey An experimental design N=32 rats and their 40-newborn offspring GA a = NA Progesterone, prolactin, and estrogen levels in the 900, 1800, and 2450 MHz/1hr groups were lower compared to the control group (p<0.001, p < 0.05, and p<0.05 respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, people, especially pregnant women and children should be cautious around such equipment until there are sufficient data. Some animal studies have recently indicated that RFR exposure during pregnancy induced some adverse effects on infants [13][14][15]. On the other hand, in a human pregnancy study, it is reported that RFR exposure during pregnancy caused significant changes in some biochemical parameters of cord blood [16].…”
Section: Oxidative Stress Parametersmentioning
confidence: 99%
“…To further disintegrate the cells, the suspension was sonicated with an ultrasonic cell disrupter (MP FastPrep-24 Tissue and Cell Homogenizer, USA). The homogenates were then centrifuged for 15 Umbilical blood samples and analysis…”
Section: Placental Tissue Samples and Analysismentioning
confidence: 99%
“…Radiation is examined in two groups as ionizing and nonionizing radiation. Radiation has negative effects on all living organisms (Goodman, Copplestone, Laptev, Gashchak, & Auld, 2019;Molu et al, 2016;Seawright et al, 2019;Zarei, Vahab, Oryadi-Zanjani, Alighanbari, & Mortazavi, 2019). These adverse effects are related to the dose of radiation exposed and the duration of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that radiation exposure causes DNA damage and is a risk factor for many cancers as leukemia, lymphoma, lung, bone, liver and kidney cancers (Behjati et al, 2016;Jacob et al, 2004;Kiang & Olabisi, 2019). Also, exposed radiation dose has been shown to increase all causes of death (Kiang & Olabisi, 2019;Seawright et al, 2019;Zarei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%